How do we respond to climate security crises in Africa? - Schapendonk, Frans; Caroli, Giulia; Pacillo, Grazia; Läderach, Peter R.D. (CGIAR FOCUS Climate Security, 2021)
The climate crisis, and the security challenges it compounds, is no longer a hypothetical concept. For millions of individuals, households, and communities across the globe, climate change has already translated into very real threats to livelihoods, health, and physical security. Africa in particular emerges as disproportionately vulnerable to compounded climate and security risks. While we should avoid making continent-wide generalisations, it’s notable that over a quarter of the world’s 40 most climate-vulnerable countries are located in Africa, 4 of which were located in the top 10 as of 2019 (Eckstein, Kunzel and Schafer, 2021). Similarly, over 23 of the world’s 40 most fragile countries are located in Africa, 6 of which are located in the top 10 (Fragile States Index, 2021).